Borderland City in New India Frontier to Gateway - McDuie-Ra, Duncan (Amsterdam University Press, 2016)
While India has been a popular subject of scholarly analysis in the past decade, the majority of that attention has been focused on its major cities. This volume instead explores contemporary urban life in a smaller city located in India's northeast borderland at a time of dramatic change, showing how this city has been profoundly affected by armed conflict, militarism, displacement, ethnic tensions, and the expansion of neoliberal capitalism.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: Political Science; Political science; Electronic books